Ultrasonic cleaning line walker for high voltage power line insulators - Ramos, Toriq (Cape Peninsula University of Technology, 2018)
This study investigates the feasibility to clean the insulators on live high voltage power lines autonomously, using ultrasound. Faulty and contaminated insulators on high voltage power lines cause flashovers, which contribute to load shedding and expensive repairs. Turning off the power in order to perform maintenance or clean insulators is a concern as it disrupts nearby businesses and homes. Regular maintenance of equipment on High voltage transmission lines (HVTL) is required to avoid major faults, thus saving money, and minimizing the pressure on the grid. Advancements in the field of robotics have catered for a solution to this concern. The study is divided into two sections; cleaning insulators using ultrasound and a line walker to navigate the high voltage transmission lines. The cleaning station was developed using a peculiar ultrasonic delivery method. The transducer is suspended 2 mm above the insulator and water is pumped into the gap between the two surfaces. The ultrasound is then applied to a small volume of water trapped by the face of the transducer using the phenomenon known as water surface tension or skin effect. A 12 V generator controlled by a Pulse Width Modulation (PWM) circuit delivers over 300 V peak to peak to the transducer via a push pull transformer. The station is equipped with a 28 kHz piezoelectric transducer governed by an admittance locking routine. The generator tracks the resonant frequency of the transducer to ensure maximum power is utilised for cleaning the contaminated area.. This peculiar delivery technique effectively cleans insulators contaminated with grease, boasts short cleaning times, and only requires a small quantity of water. A four wheeled line walker was then designed in order to transport the cleaning station to the contaminated insulators. Each wheel propels the line walker forward at 0.1 m/s, and a uniquely shaped leg mechanism couples them to the chassis. The four legs are capable of independently removing the wheels from the line to avoid obstacles, and a 16-bit Atmega 2560 microcontroller monitors and controls all on-board devices and moving parts. Limit switches, an accelerometer and an ultrasonic distance sensor allow the robot to navigate around obstacles such as strain clamps, vibration dampers and indicating spheres. The line walker is capable of maintaining a balanced horizontal position while navigating the line. A scaled prototype of the line walking robot was manufactured and tested in a laboratory environment. The results prove that the robot can effectively navigate around obstacles while the system is run completely autonomously. The study provides proof of concept and enough evidence to suggest that the ultrasonic cleaning line walker is a feasible project with great potential.
Thesis (MEng (Electrical Engineering))--Cape Peninsula University of Technology, 2018